Digitalisasi Operasional UMKM Indekos: Implementasi Aplikasi Manajemen Penghuni, Pembayaran, dan Keluhan di Kota Medan - Ali Akbar Lubis; Frans Mikael Sinaga; Riche Riche; Ade Sarah Huzaifah; Jefri Junifer Pangaribuan (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2025)
MSME 'Indekos' (boarding houses) in Medan City are generally still managed manually, causing partners to face fundamental problems in service and administration. The billing process, reliant on face-to-face meetings, makes tracking payments difficult, while tenants are often late paying due to a lack of reminders. Furthermore, the absence of a documented complaint channel means owners often forget to follow up on issues. This community service (PKM) activity aimed to overcome these problems through operational digitalization. The priority problems addressed were (1) the digitalization of billing and payments to provide real-time arrears information, and (2) the provision of a documented complaint channel with status tracking. The PKM method involved Training and Mentoring for 3 'indekos' owners in Medan City. The science-and-technology (ipteks) solution, a web-based management application, was developed using the adaptive Extreme Programming (XP) methodology, allowing iterative improvements based on partner feedback. Implementation included business process mapping (Planning), application installation (Small Releases), and guided testing (Testing/Feedback). The result of this activity is a ready-to-use application (PHP/MySQL) delivered to partners, along with operational SOPs and training modules. The implementation successfully improved the owners' administrative efficiency and service transparency for tenants.